Development of chicken patties incorporated with onion (Allium cepa) and beet root (Beta vulgaris) extract powder - Nagre, Shubhangi S; Chappalwar, Anita M; Rindhe, Sandeep N; Londhe, Sanjay V; Nikam, Mahalsakant G (Journal of Meat Science, 2023)
Meat and meat products are dense source of nutrients, having health and industrial importance. However nutrient rich meat and its products have low stability even at low temperature. Application of natural antioxidants to perishable food product for enhancing stability is an innovative concept. Therefore the present study was planned to develop chicken patties incorporated with different levels 0.75, 1.5 and 2.25% of onion or beet root extract powder. From the study, it is observed that the pH and cooking yield values were decreased significantly in onion and beetroot extract treated patties respectively. Moisture, fat, protein content decreased significantly (P<0.05), however ash content increased with increase in the level of onion and beetroot extract incorporation in chicken patties. Sensory study revealed that the 1.5% onion and beet root extract powder treated chicken patties had significantly (P<0.05) higher sensory scores for all attributes than control and other treatments, showing liking of consumers for 1.5% onion extract powder treated patties.